CCAFS site atlas – Lawra – Jirapa / Lawra - Sijmons, Koert; Kiplimo, Joyce; Förch, Wiebke; Thornton, Philip K.; Moussa, Abdoulaye S.; Zougmoré, Robert B. (2013)
CCAFS site atlas for Lawra – Jirapa / Lawra, Ghana.